If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 5x = 6 + 3x Solving 4 + 5x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + 5x + -3x = 6 + 3x + -3x Combine like terms: 5x + -3x = 2x 4 + 2x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 4 + 2x = 6 + 0 4 + 2x = 6 Add '-4' to each side of the equation. 4 + -4 + 2x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 6 + -4 2x = 6 + -4 Combine like terms: 6 + -4 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 4y+8=-26 | | 33+7x+10=13+2x | | 3.5(x+4)+4.5=2(-6.5) | | .66(1+n)=-.50n | | |-3a|=15 | | x^2+10+24= | | y=2/3(-1)-7 | | 9.06=51 | | -62u=60 | | 2y+6=-8 | | (x+4)(x-2)=7 | | y=2/3(1)-7 | | y=2/3(0)-7 | | 6b-38=-6b+14 | | 3(2x+1)=4x-13 | | 54=(4r-5) | | 8(f+8)=1 | | 2a-5(a-4)=-4 | | X+3x-12=180 | | 7=2t-5 | | X(3x-12)=180 | | 4x+(5+2x)=2 | | 5x+18-4=-36 | | x^2+6-30=0 | | 2r-45-19r=-53+r | | w-6=-48 | | y=4+(-2) | | -10-6x+4x=3-4x-1 | | 2x+y=39.50 | | w-6=48 | | y=8-3/4(-1) | | 4=6(x-2)-8x |